Correspondence Course : An Epistolary History of Carolee Schneemann and Her Circle - Schneemann, Carolee, 1939-2019 (Book collections on Project MUSE., 2010)
An epistolary history of the international avant-garde of happenings, Fluxus, and performance and conceptual art emerges from decades of correspondence between Carolee Schneemann and other artists and intellectuals.